Efeitos da exposição ao cloreto de mercúrio (HgCl2) sobre a qualidade e capacidade fértil de espermatozoides bovinos - Silva, Elane Fabíola de Sousa Jerônimo da (2016)
Hg is a toxic heavy metal, bioaccumulative and of global concern, since its anthropogenic and natural emissions still pose a high risk for human and environmental health. Hg may cause impairment of male fertility, however, most studies have evaluated high dose exposure. In this sense, the adverse effects generated by low dose Hg in the male reproductive system are little elucidated and the use of the bovine model, due to the great similarity to the human, can contribute to this toxicological evaluation in this system. The objective of this work was to investigate the effects of mercury chloride (HgCl2) exposure at different concentrations on bovine spermatozoa and its fertilization capacity. Bos taurus semen straws were thawed, spermatozoa selected by discontinuous Percoll® gradients (4x106 sperm/mL) and divided into: Control (without exposure to HgCl2); Hg8nM; Hg8μM and Hg80μM, incubated for 0.5h, 1h and 2h. After the exposure, sperm parameters (motility, vigor, computerized sperm kinetics, morphology, sperm membrane integrity) and oxidative stress biomarkers were analyzed. For the analysis of in vitro fertilization, bovine oocytes matured for 24h and, after 18 hours of co-culture of oocytes/spermatozoa (2x106 spermatozoa/mL), total and normal penetration and fertilization rates were evaluated. Exposure of bovine spermatozoa at different concentrations of HgCl2 was able to reduce sperm motility, increase the minors defects (Hg80μM), reduce the number of normal spermatozoa (Hg80μM and Hg8μM) and affect the integrity of the plasma membrane (Hg8μM). Regarding the biochemical biomarkers evaluated in the low doses of this metal, there was an increase in the reactive oxygen species and lipid peroxidation and reduction of the total antioxidant capacity in both doses (Hg8nM and Hg8μM) analyzed. As for fertilization, there was a reduction in the penetration rate and total and normal fertilization of the Hg group with the concentration of 8μM. Exposure of bovine spermatozoa at low concentrations of Hg favors the increase of oxidative stress that can trigger changes in sperm quality and reflect in the reduction of their capacity of IVF.